EUGENICS: SCIENCIE AND RELIGION. AN APPROACH TO THE CHILEAN CASE - Sánchez Delgado, Marcelo (Revista de Historia Social y de las Mentalidades, 2024)
The work aims to investigate the relationships of  continuity and tension between the modern project,  religious thought and the eugenic thinking in the  Chilean context.  The work begins with a general reflection on the  relationship between eugenics and religion in the  modern context, and then engages with primary  sources that includes works by lawyers and  physicians of the first half of the chilean twentieth  century. The main result of the study shows that the  discussion of eugenic thought in the national  context was no stranger to religious, utopian  and mystifying forces, which tends to see  eugenics as the religion of the future and as a  thinking alternative and critical of Christianity.  Moreover, also stands out as a result of this work,  a new appreciation of the relationships between  Catholicism and eugenics in the Chilean context.
Keywords: Eugenics; modernity; religion; Latin America; Chile